2019
DOI: 10.5296/jei.v5i2.15603
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Health Beliefs of Physical Education and Sports Teachers Regarding Sportive Recreational Activities

Abstract: This paper aimed to analyze the health beliefs of physical education and sports teachers regarding sportive recreational activities in the extent of their socio-demographic features. The study sample consisted of 286 (101 male & 185 female) physical education teachers. In the study to collect data, we used the "Health Belief Scale for Sportive Recreational Activities" scale. In analyze of the data, first, we calculated Cronbach's Alpha, Skewness and Kurtosis values. Then we used One Way Anova and Independent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
(11 reference statements)
1
4
0
Order By: Relevance
“…Although it was determined that there were significant differences between genders and participation in recreational activities, no significant differences were found between genders and the sub-dimensions concerned. The results of this study show parallelism with the results reported by Kayhan and Üstün [ 34 ], who examined the relationship between genders of physical education and sports teachers and the HBSSRA sub-dimensions, and found that there was no significant difference between genders of the participants in terms of any of the sub-dimensions. They evaluated this result as that male and female teachers have similar health beliefs in sportive recreational activities.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Although it was determined that there were significant differences between genders and participation in recreational activities, no significant differences were found between genders and the sub-dimensions concerned. The results of this study show parallelism with the results reported by Kayhan and Üstün [ 34 ], who examined the relationship between genders of physical education and sports teachers and the HBSSRA sub-dimensions, and found that there was no significant difference between genders of the participants in terms of any of the sub-dimensions. They evaluated this result as that male and female teachers have similar health beliefs in sportive recreational activities.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, different from this study, the researchers determined that there were significant differences between the marital status and the Perceived barriers sub-dimension scores. This result shows that there are differences in health beliefs in terms of marital status between this study, conducted with healthcare professionals, and the study conducted with physical education and sports teachers [ 34 ]. It is understood that the marital status of teachers is not a barrier to the realization of sportive recreational activities.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Regarding epistemic beliefs about the health concept, some studies report a somewhat biomedical perspective on health of PE teachers, as reflected in the 'healthism' ideology (Alfrey et al, 2019;Wright et al, 2018). (Pre-service) PE teachers in these studies have a "medico-scientific view of health imbued with individualised, risk discourses" (Wright et al, 2018, p. 117) and focus on PA and nutrition behavior as important aspects of individual health (Kayhan & Üstün, 2019;Wilkinson et al, 2014). Others show that pre-service (Welch & Wright, 2011) and in-service (Harris & Leggett, 2015a) PE teachers are also critical of the healthism concept.…”
Section: Inventory Of Beliefs Attitudes and Philosophies Of Pe Teachersmentioning
confidence: 99%